Optimization of distillation column reflux ratio for distillate purity and process energy requirements - Fitriah Fitriah; Dessy Agustina Sari (International Journal of Basic and Applied Science, 2023)
Recovering ethanol solutions from filtration, extraction, and stripping operations is done in the distillation column, a separation process unit in the carboxymethyl cellulose production plant. Because the ethanol produced by these techniques is produced at a lower concentration, distillation is required to purify the ethanol. This procedure can raise the concentration of ethanol by separating it from the mixture. The concentration of the ethanol solution needs to be 85% in order to be reused. This case study aims to determine the optimal reflux ratio for a distillation column, model the process in both real-world and manual calculation scenarios using Aspen Hysys software, and evaluate the effects of increasing the reflux ratio. Manual computations yielded a reflux ratio result of 0.91814. In the meantime, an ethanol concentration of 85% is produced by the reflux ratio of 1.080 that is derived from the Aspen Hysys simulation. By generating a heat flow of 1.889 x 106 kJ/h, the ideal reflux ratio of 1.080 was reached, whereas the Aspen Hysys simulation yielded a reflux ratio of 0.91814. This allowed for an ethanol concentration of 85%. The Aspen Hysys simulation yields an ethanol concentration of 82.11% and a heat flow of 1.399 x 106 kJ/h. The ethanol concentration and reboiler steam heat flow are impacted by the reflux ratio value, according to the reflux ratio results. The amount of reboiler steam heat generated may become linear with a larger reflux ratio, and the energy required to complete the distillation process may likewise rise.